Edukasi Asuhan Mandiri Tanaman Obat Keluarga dan Keterampilan Akupressure pada Ibu untuk Manajemen Keluhan Ringan Pada Kelompok Ibu Majelis Taklim - Sujati, Ni Ketut; Fadhilah, Laila; Rustiati, Nelly; Mahafira, Nesa Dwi; Prawiti, Ayu Dwi; Rafela, Sindi; Akbar, M Agung (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Family health is a crucial aspect of community life, with mothers playing a key role in managing minor health complaints such as headaches, muscle pain, and digestive issues. Traditional methods like Family Medicinal Plants (TOGA) and acupressure offer effective, low-cost solutions. Objective: This community service program aimed to educate and train mothers in the Majelis Taklim on self-care management using TOGA and acupressure techniques to address minor health complaints. Method: The program employed a participatory approach, conducted in three stages: preparation (March–May 2024), implementation (June–October 2024), and evaluation (November 2024). Activities included TOGA education, acupressure training, safety discussions, holistic lifestyle counseling, and community forums. Quantitative (pre-test/post-test) and qualitative (observation, satisfaction surveys) evaluations were used to measure outcomes. Result: The program significantly improved participants' knowledge and skills, with 70% reporting high effectiveness of TOGA for minor ailments. Daily TOGA usage increased to 45%, and 65% of participants shifted from chemical drugs to natural remedies. Challenges included material availability (40%) and processing techniques (30%). Participant satisfaction reached 85%, and 60% disseminated knowledge to their communities. Conclusion: The program successfully enhanced mothers' capacity in self-health management using TOGA and acupressure. Continued support, such as mentoring groups and community TOGA gardens, is recommended for sustainability.